PERSPEKTIF SOSIOLOGIS SISTEM DAN STRATEGI PENGEMBANGAN PARIWISATA - Prof. Dr. RB. Soemanto, MA. (UNIVERSITAS SEBELAS MARET (UNS), 2018)
Tourism development requires potential tourism of the societies which is the basis of tourism service development strategy. Problems arise in the internal and external conditions of tourism. The development of tourism requires the readiness and quality of tourism services. The prime tourist service becomes a prerequisite for tourism success. The answer to the question of what, why, who and how in the tourism development become the cornerstone of sustainable tourism development. The development strategy is mobilizing and empowering all potential tourism to support the implementation of tourism programs. The Government institutions, tourism actors, and elements of the community who cooperate to implement policies and programs of tourism development to strengthening the prime tourist services. Because the quality of tourist services is key of the tourists satisfaction. Keywords: sociology, system, strategy, tourism development AbstrakPengembangan pariwisata membutuhkan potensi kepariwisataan yang menjadi dasar strategi pengembangan layanan wisata. Permasalahan timbul pada kondisi internal dan eksternal kepariwisataan. Pengembangan kepariwisataan memerlukan kesiapan dan mutu layanan wisata. Layanan wisata prima menjadi syarat keberhasilan pariwisata. Jawaban pertanyaan: apa, mengapa, siapa dan bagaimana dalam pengembangan pariwisata menjadi landasan pengembangan pariwisata keberlanjutan.. Strategi pengembangan itu bersifat menggerakkan dan memberdayakan seluruh potensi dan menghidupi pelaksanaan program-program kepariwisataan. Pemerintah, pelaku wisata, dan unsur masyarakat yang bekerjasama melaksanakan kebijakan dan program pengembangan pariwisata menguatkan layanan wisata prima. Dan kualitas layanan wisata menjadi kunci bagi kepuasan wisatawan. Kata Kunci: sosiologi, sistem, strategi, pengembangan parisiwata